Catalytic Pyrolysis of Biomass to Synthesize Bio-oil and Chemicals: A Review - Mohd Ridzuan Nordin; Nugroho Dewayanto (Universitas Ahmad Dahlan, 2016)
Increasing of global energy demand and depletion of fossil fuels reserves encourage people to search alternative energy resources. Biomass becomes promising candidate as alternative energy sources since their sustainability. Pyrolysis is one of method to convert biomass into bio-fuel. Almost all of biomass materials can be converted into products by pyrolysis process. However, quality of bio-oil produced by pyrolysis is still considered as low quality, due to their high oxygen content and acidity. This paper provides a critical review of catalytic pyrolysis of biomass to produce bio-oil with better properties. Types of catalysts are discussed in this manuscript, as well as their capability to reduce the oxygen content of product and enhance the properties of bio-oils.